The effect of adjunctive low-dose doxycycline and licorice therapy on gingival crevicular fluid matrix metalloproteinase-8 levels in chronic periodontitis - Shirin Zahra Farhad; Atousa Aminzadeh; Morvarid Mafi; Mehrdad Barekatain; Mohammad Naghney; Mohammad Reza Ghafari (Wolters Kluwer Medknow Publications, 2013)
Background: This study compared the effect of adjunctive low dose doxycycline and licorice on gingival crevicular fluid (GCF) matrix metalloproteinase-8 (MMP-8) levels in patients with chronic periodontitis. Materials and Methods: In this in vivo, experimental study 39 patients with mild to moderate chronic periodontitis were selected. Samples of GCF were collected from three deepest pockets and MMP-8 concentration was measured. Patients were divided into three groups (n = 13). Groups were treated with doxycycline, licorice and placebo. Sampling and measurement of MMP-8 was repeated after 6 weeks. Data was analyzed by t-paired and ANOVA test. P < 0.001 was considered significant. Results: The decrease in mean of MMP-8 concentration was higher in doxycycline and licorice group in comparison with the placebo group and the difference was statistically significant (P value < 0.001). The decrease in mean of MMP-8 concentration was higher in licorice group than doxycycline group, but the difference was not statistically significant. Conclusion: The present study showed that licorice extract can prevent the production of MMPs by host cells and can be as useful as antibiotics like doxycycline to cure periodontal and other inflammatory diseases. It must be added that no side-effects were observed in usage of licorice extract.